KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PERUSAHAAN NON-KEUANGAN - Satriana Gandamihardja; Ellen Rusliati (JRAK, 2020)
A phenomenon in the company’s strategy in carrying out business development is mergers and acquisitions. In fact, the company prefers acquisition as its strategy, but it still lacks synergies after making acquisitions. The purpose of this study is to compare the financial performance before and after the acquisition of non-financial companies listed on the Indonesia Stock Exchange in 2012. The population are 31 companies that make acquisitions. The method used is descriptive and verification methods, with paired sample t-test. Based on the hypothesis test, the results showed that the current ratio, total asset turnover, debt to equity ratio did not have a significant difference between before and after the company made the acquisition, while the return on assets has a difference, but was decreasing. The acquirer needs to measure the performance of the company being acquired and project the performance and risk after the acquisition.